2022
DOI: 10.1101/2022.07.11.499665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural Variation in Diauxic Shift between Patagonian Saccharomyces eubayanus Strains

Abstract: The study of natural variation can untap novel alleles with immense value for biotechnological applications. Saccharomyces eubayanus Patagonian isolates exhibit differences in the diauxic shift between glucose and maltose, representing a suitable model to study their natural genetic variation for novel strains for brewing. However, little is known about the genetic variants and chromatin regulators responsible for these differences. Here, we show how genome-wide chromatin accessibility and gene expression diff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Previous studies using hybridization and experimental evolution demonstrated that Lager yeast hybrids could be improved through selection under fermentation conditions (Krogerus, Preiss, et al, 2018) without polyploidization (Krogerus et al, 2015). While these studies have expanded the diversity of Lager yeast phenotypes, they are primarily based on a single S. eubayanus genetic background, CBS 12357T (belonging to PB-1), which is not representative of the overall species' genetic and phenotypic diversity (Burini et al, 2021;Molinet, Eizaguirre, et al, 2022;Nespolo et al, 2020;Urbina et al, 2020). S. eubayanus lineages vary widely in fermentation capacity and aroma profiles during beer fermentation, suggesting that the natural diversity of S. eubayanus is also well-suited for making innovative Lager hybrid strains (Burini et al, 2021;Mardones et al, 2021;Urbina et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies using hybridization and experimental evolution demonstrated that Lager yeast hybrids could be improved through selection under fermentation conditions (Krogerus, Preiss, et al, 2018) without polyploidization (Krogerus et al, 2015). While these studies have expanded the diversity of Lager yeast phenotypes, they are primarily based on a single S. eubayanus genetic background, CBS 12357T (belonging to PB-1), which is not representative of the overall species' genetic and phenotypic diversity (Burini et al, 2021;Molinet, Eizaguirre, et al, 2022;Nespolo et al, 2020;Urbina et al, 2020). S. eubayanus lineages vary widely in fermentation capacity and aroma profiles during beer fermentation, suggesting that the natural diversity of S. eubayanus is also well-suited for making innovative Lager hybrid strains (Burini et al, 2021;Mardones et al, 2021;Urbina et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Hybrids and parental strains were phenotypically characterized under microculture conditions as previously described (Molinet, Urbina, et al, 2022). Briefly, we estimated mitotic growth in 96-well plates containing Yeast Nitrogen Base (YNB) supplemented with 2% glucose, 2% maltose, 2% maltotriose, 2% glucose and 9% ethanol, 2% glucose and 10% sorbitol, and under carbon source switching from glucose to maltose as previously described (Molinet, Eizaguirre, et al, 2022). All conditions were evaluated at 25 °C.…”
Section: Phenotypic Characterizationmentioning
confidence: 99%
See 1 more Smart Citation